Rheumatoid arthritis in Colombia: a clinical profile and prevalence from a national registry (2021)
Background There is a need to describe the demographic and clinical characteristics of people diagnosed with rheumatoid arthritis who are attended within the Colombian health system. This characterization allows prioritizing populations with specific risks, programming the use of health services, and planning the costs necessary to guarantee equitable care. Objective To assess the demographic and clinical characteristics of a cohort of patients with rheumatoid arthritis using national data collected by the High-Cost Disease Fund (CAC in Spanish). Methods A cross-sectional study from a secondary source. Data was gathered from a national administrative registry. A descriptive analysis was performed on sociodemographic and clinical characteristics. Age-standardized prevalence was estimated at national level and by geographical regions. Remission rates were also estimated for Colombian departments and regions. Results By 2019, 81,386 patients with rheumatoid arthritis were reported in Colombia. The relation female-male was 5.2:1. The median age was 59 years (IQR: 50–67). Prevalence was higher in people aged 50–69 years. The most frequent comorbidities were high blood pressure (31.15%) and osteoporosis (19.46%). Age-standardized prevalence of rheumatoid arthritis was 0.24 per 100 population (95% CI: 0.23–0.24). In cases with complete information, 57.57% of departments had remission rates up to 30%. Conclusion Rheumatoid arthritis in Colombia was more frequent in females aged ≥50 year. Age-standardized prevalence was lower than reported by other studies performed in Colombia but similar to the estimated internationally for the country.